The role of IL-18 and IL-33 in the bronchoalveolar lavage fluid of children with severe community-acquired pneumonia complicated with pleural effusion - Zhang, Yinxia; Liu, Zihao; Hong, Yiwei; Li, Li; Liang, Youzhuo; Lin, Liangxin; Wang, Wenjian; Wang, Heping (Frontiers in Pediatrics, 2025)
BackgroundTo investigate the evaluative role of interleukin (IL)-1 family cytokines in bronchoalveolar lavage fluid (BALF) among children with severe community-acquired pneumonia (SCAP) and identify cytokines with clinical relevance for pediatric SCAP.MethodsChildren with SCAP hospitalized at Shenzhen Children's Hospital (2019–2020) were studied. IL-1 family cytokines in the BALF were measured via CBA or ELISA. These cytokines included nine IL-1 family members (IL-1α, IL-1β, IL-1Ra, IL-33, IL-18, IL-37, IL-36α, IL-36Ra, and IL-38) and two receptors (sST2 and IL-18BP). The ratio of proinflammatory cytokines to anti-inflammatory cytokines was analyzed.ResultsIn the BALF of children with SCAP complicated with pleural effusion (PE), the levels of IL-18, the IL-18/IL-38 ratio, and the IL-33 level were significantly elevated (P < 0.05). Furthermore, the receiver operating characteristic (ROC) curve indicated that these three markers have strong predictive efficacy for diagnosing SCAP complicated with PE. The levels of members of the IL-1 family, including IL-1α, IL-1β, IL-1Ra, IL-18, and IL-33, and their associated ratios significantly differed across different pathogen groups (P < 0.05). IL-36α and the IL-36α/IL-38 ratio differed significantly between the Haemophilus influenzae (Hi)-positive and -negative groups (P < 0.0001 and 0.0048), with lower levels in the Hi-positive group.ConclusionIL-18, IL-33, and IL-38 in BALF may serve as effective markers for predicting the development of PE in pediatric SCAP patients. Additionally, respiratory tract colonization by Hi may diminish the production of specific proinflammatory cytokines, including IL-18, IL-33, and IL-36α, during SCAP.